Utah's IBIS-PH: an innovative user interface solution for Web-based data query systems. - Braithwaite G; Haggard LM (Journal of Public Health Management & Practice)
The ability to make good Web-based data query system (WDQS) project management decisions requires an understanding of the trade-offs inherent among various technology options. This article presents the current options available for the user interface and data display and compares the advantages and disadvantages of each for use in a WDQS. Relevant options are also discussed for back-end technologies such as Web and application servers and data storage mechanisms. We explain our decisions in developing the Indicator-based Information System for Public Health (IBIS-PH) query system to increase the probability of success and minimize risk. Finally, we compare the resulting IBIS-PH application characteristics with our original design requirements: broad public access; rich, interactive, and easy-to-use interface; portability; accessibility; maintainability of software and interface; supportability; low cost; and security.